Infaq Tube Pick Up Scheduling Application in Pontianak City Based on Android (Case Study of West Kalimantan Lazismu) - Rizal Basri; Yus Sholva; Haried Novriando (Jurusan Informatika Universitas Tanjungpura, 2022)
The Amil Zakat Infaq Shadaqah Muhammadiyah Kalbar Institute (LAZISMU Kalbar) is a national-level zakat institution that is solemn in empowering the community through productive utilization of zakat funds, infaq, waqf and other philanthropic funds from individuals, institutions, companies and other agencies. Lazismu Kalbar has several programs, one of which is the infaq tube, which is a charity box program as a means to make it easier for donors to donate and give charity in their respective homes. The collection of infaq funds by West Kalimantan LAZISMU officers is carried out once or twice a month according to the time agreement between the donor and the West Kalimantan LAZISMU. Considering that the number of donors continues to grow, it is difficult for officers to arrange the pick-up times for the charity boxes, besides that the officer's journey becomes inefficient because the charity boxes that should be taken at once in one trip are forced to take two trips to places that are actually close to each other. A system and application is needed that is able to support the charity box pick-up process with a scheduling mechanism. This research has developed an Android mobile application that makes it easier for LAZISMU officers to schedule pick-up for the infaq tube, which is very important, in order to minimize the possibility of clashing pick-up schedules. Making the application using IDEA Android studio with web service as its database technology, which utilizes google calendar technology as a scheduling medium and utilizes notifications from google calendar as notification of infaq tube pick-up notifications. Based on the test results, in compatibility testing, the application is installed and runs well on android devices starting from the Jelly Bean operating system version (4.2.2) to Pie (9.0).